Development of a questionnaire on intentions to engage in dating violence among Puerto Rican residents - Padilla Medina, Diana M. (Journal of family violence, 2022)
This mixed-methods paper describes the development and preliminary validation of the Behavioral Intentions Questionnaire (BIQ), a multi-scale questionnaire developed to assess determinants influencing Puerto Rican adolescents’ intentions to engage in abusive behaviors in dating relationships. Items were developed qualitatively, and face and content validity were established by expert and target population judges via semi-structured interviews (n = 48), discussions, and four focus groups (n = 6 each). The questionnaire was pilot tested twice. An initial pilot test was conducted with students aged 13 to 17 from a private alternative education program in San Juan, Puerto Rico (n = 32). A second pilot test was conducted with a sample of students from the same site (n = 22), in addition to students in the same age range from a private school (n = 88) in San Juan. Confirmatory and Exploratory factor analysis was used to determine construct validity and Cronbach's coefficient alpha determined the subscales internal consistency reliability. Correlations between subscales were examined. Thematic content analysis was used to analyze qualitative data. Qualitative data suggested the need to revise or eliminate items and instructions and incorporate a social desirability measure. Factor analyses yielded a unidimensional structure for each subscale and each subscale demonstrated high internal consistency. Preliminary analysis on the factor structure, internal reliability, and validity of the BIQ were encouraging. However, further psychometric testing is needed before this measure can be considered a useful tool for measuring intentions to engage in abusive behaviors in dating relationships.